Penggunaan Media Audio Visual Dalam Meningkatkan Hasil Belajar Al-Qur’an Hadits Pada Siswa Kelas VIII Madrasah Tsanawiyah Hujjaturrahmah Tanjung Pura - Anisa Fahira Tanjung, Anida, Ahmad Fuadi (CV. PUSDIKRA MITRA JAYA, 2023)
This is due to the implementation of learning Al-Qur'an Hadith not using media audio-visual is considered as an innovative medium so that learning and teaching activities are considered as learning activities with classical methods and tend to be conventional so that the implementation of learning becomes monotonous which of course can affect students' learning outcomes of Al-Qur'an Hadith. The problems found at the research location are as follows: Whereas the application and development of Audio Visual media has not been implemented optimally, this is because teaching and learning activities are more dominantly carried out in the conventional way, namely teaching and learning activities carried out with lecture techniques. Whereas learning that leads to the use of Audio Visual media is very limited in the availability of electronic devices and media. Based on the problems mentioned above, the authors use the Classroom Action Research method to determine whether there is an increase in learning using audio-visual media in the field of study of the Al-Qur'an Hadith. The implementation of this research consisted of 3 (three) cycles, each cycle the researcher used a test instrument to determine the completeness of students' scores in learning. The conclusion in this study is that the use of Audio Visual Media in improving students' memorization in the field of Al-Qur'an Hadith for Class VIII students of Madrasah Tsanawiyah Hujjaturrahmah has been well implemented and there has been an increase since the beginning of the pre-cycle, namely the number of students who get the average completeness score, namely 53.78 students who received a complete score in the field of Al-Qur'an Hadith, in Cycle I increased to 67.75 students who completed the Al-Qur'an Hadith learning activities on rote material. In Cycle II the level of student completeness in learning Al-Qur'an Hadith was 74.6 in Class VIII of Madrasah Tsanawiyah Hujjaturrahmah. Then analyzed from Cycle III the student completeness reached 83.7. So, it can be concluded that the use of audio-visual media can improve student learning outcomes in class VIII Madrasah Tsanawiyah Hujjaturrahmah.